If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 5) + 7 = 31 Reorder the terms: 8(5 + x) + 7 = 31 (5 * 8 + x * 8) + 7 = 31 (40 + 8x) + 7 = 31 Reorder the terms: 40 + 7 + 8x = 31 Combine like terms: 40 + 7 = 47 47 + 8x = 31 Solving 47 + 8x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + 8x = 31 + -47 Combine like terms: 47 + -47 = 0 0 + 8x = 31 + -47 8x = 31 + -47 Combine like terms: 31 + -47 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 216-3x=42x+21 | | 13-9x=43-23x | | 21-3*(2x-5)=12 | | 3q^2-16q+23=P | | 5(e-7)=1 | | 8y^2-75y+175=0 | | 3t+6t-5=34 | | 2x^2+13x-7=0 | | x+6*4=17 | | 4x+14=63-3x | | -3(y-4)=-4y | | 4x+34=6x+12 | | 4a-4.8=2.4-2a | | 3(n-5)-(6-2n)=4n | | 6.4-5y=y+2.8 | | 3x-12=4x-8 | | 24-x=-13 | | 2p-9=5p+12-5w | | 35-y=4y | | 2s+16=s-25 | | 14-(2c+5)=-2c+9 | | 20-16p=4(5-4p) | | 4n+8=8-4n | | -7+8(5-3s)=3(7-9s) | | 4g+3(g-2)=-5(g-4)-g | | 2b+4(b-6)=-2(2b-14)+98 | | 1.4h=1.8h+4.8-0.4h | | 3b+16=5b+16-2b | | 4m-(8-m)=6-2m | | 4u-7=u+3(4+u) | | y-2y+3=3-y | | 4n-14=-16n+26 |